Pengaruh pola kepemimpinan dan komitmen organisasi terhadap disiplin kerja dengan karakteristik pekerjaan sebagai variabel intervening pada rumah makan tradisional food Dapur M’riah Mojokerto Jawa Timur - Ainurrofiq (FADZAT: Jurnal Ekonomi Syariah, 2022)
The aims of this research are: 1) Analyzing the pattern of leadership on job characteristics. 2) Analyzing the effect of organizational commitment on job characteristics. 3) Analyzing the influence of leadership patterns on work discipline. 4) Analyzing the effect of organizational commitment on work discipline. 5) Analyzing the effect of work discipline on job characteristics. 6) Analyzing the influence of leadership patterns indirectly on work discipline through job characteristics. 7) Analyzing the influence of organizational commitment indirectly on work discipline through job characteristics. The population in this study were all employees at the traditional food restaurant, Dapur M'riah, Mojokerto, East Java, with a total of 56 people. The sampling method used the census technique, the data analysis used the help of SPSS version 20 to test the validity with factor analysis, and test reliability with Cronbach. Classical assumption test and multiple linear regression analysis, to verify and prove the research hypothesis. From the results of the study, it can be concluded as follows: 1) Leadership pattern has no effect on job characteristics 2) Organizational commitment has a significant effect on job characteristics 3) Leadership pattern has no effect on work discipline 4) Organizational commitment has a significant effect on work discipline 5) Job characteristics have a significant effect on work discipline 6) Leadership patterns have an indirect effect on work discipline through job characteristics 7) Organizational commitment has an indirect effect on work discipline through job characteristics